A criação do conflito em narrativas literárias escritas por mulheres - Mendes, Rute Elisa Jorge (2007)
This work treats of the characterization of the conflict in literary narratives written by women, with focus in its construction. It is developed starting from an analysis model that considers the analysis of the narrative structure, based on Sayeg Siqueira's work in which he shows up the organizational aspects, the narrative course and the modalization of the characters' attitude. It also contemplates the critical analysis of the speech, grounded in Fairclough's theory that also shows the way how the practices discursive linguistic overlay sociopolitical structures more comprehensive of power and dominance and they hope to produce changes not just in the discursive practices, but also in the practices and sociopolitical structures that support the discursive practices. For that two short stories were analyzed: "Amor" (Love) by Clarice Lispector and "Venha ver o pôr-do-sol" (Came to see the sunset) by Lygia Fagundes Telles. By those considerations,we intend to show how the narrative conflict is built in texts written by women. It is considered important to establish the constitution of the feminine universe, for that we present a concise historical of the Brazilian women's situation from the colonization to the present time, it still approaches other aspects as the gender that exposes how men and women are organized social and culturally because of the individuals' sexual identity; the sexism, that reflects about the discriminatory attitudes in relation to the opposite sex; and still the ethos, with focus in the feminine ethos, that allows to consider the image that is built of itself in a speech. The feminine discursive speech assists in the formation of a new woman's image, it allows her recognition as social subject. It is evidenced the power that the social rules imposed, and still do, to the feminine papers, and it is characterized the conflict for that universe with the break of expectations caused by social pressure